Carbon Democracy at ten: an interview with Timothy Mitchell. Issue 3 (4th May 2023) - Szeman, Imre; Wellum, Caleb
ABSTRACT: With the publication of Carbon Democracy, Timothy Mitchell made a major contribution to the political study of energy resources that helped launch an exciting era of energy studies. Energy humanities scholars Imre Szeman and Caleb Wellum interviewed Mitchell in 2021 about the genesis, arguments, and legacies of Carbon Democracy. This wide-ranging conversation explores how the political context of the early 2000s informed the book, how the book has shaped the study of oil and energy, and the new directions Mitchell's research has taken since the book's publication. The conversation also includes discussion of Mitchell's methodological approach to technopolitical subjects and where the study of energy needs to go from here.